Enacting Anti-Discriminatory Pedagogy in Compulsory English Classrooms in Grades XI and XII in Nepal: Challenges and Possibilities (KMC Journal, 2025)
This study argues that the pedagogy in compulsory English classrooms for grades XI and XII in Nepal can be reoriented to actively promote justice by challenging the social problem of untouchability and caste-based discrimination experienced by the Dalits, the assumed lowest caste. The study has two objectives: to critically review legal provisions and compulsory English textbooks of grades XI and XII by tracing the caste issues, and to theorize and propose the possibilities of implementing anti-oppressive pedagogy in those classrooms. While achieving those objectives, this paper performs content analysis of the constitutional/legal provisions, the curriculum, and compulsory English textbooks from the theoretical perspective of critical pedagogy and multiliteracies. The analysis reveals that the prescribed compulsory English textbooks for grades XI and XII are neutral about the caste discrimination experiences of the Dalit identities. Therefore, this study proposes and exemplifies a possibility of pedagogical interventions against the caste discrimination faced by the Dalits. Hence, this study advocates for integrating anti-discriminatory pedagogical approaches to foster critical consciousness among students, and proposes to promote social harmony and justice across the nation.